PENGARUH AUDIT INTERNAL MANAJEMEN MUTU TERHADAP KINERJA KARYAWAN DI PT. CIPTA MANDIRI WIRASAKTI - Wuri Wuri; Suwandi Suwandi (FEB Institut Bakti Nusantara, 2022)
In this study it was found that the implementation of the internal audit had been carried out starting with coordination up to the plan of the internal audit report to the Board of Directors. The actual implementation is backwards from the initial plan which results in the next step being also disrupted. Because the audit was not carried out on time, it required more coordination between the auditor and the auditee and resulted in the delay of audit verification and reporting to the Board of Directors one month from the initial planned schedule. With delayed implementation, the benefits of improving audit findings are also less pronounced. This study aims to analyze the effect of quality management internal audit on employee performance at PT. Cipta Mandiri Wirasakti. The research method used is quantitative research methods. Data collection techniques using a questionnaire. The total population is 103 people with a sample of 82 people (deviation 5%). This study uses data analysis methods consisting of Validity Test, Reliability Test, Classical Assumption Test (Normality Test, Heteroscedasticity Test and Autocorrelation Test), Simple Linear Regression Analysis, Hypothesis Testing and Coefficient of Determinants. The results of the study with the help of SPSS 23.0 program calculations obtained the t-count value of 6.328 while the t-table was 1.66412 with R Square of 0.334. Thus, the independent variable, namely internal audit quality management, has a positive influence on the dependent variable of employee performance by 33.4%.